PERANAN METODE DISKUSI KELOMPOK TERHADAP PENINGKATAN KEMAMPUAN SISWA DALAM PEMBELAJARAN BAHASA INDONESIA KELAS X MIA 3 SMA NEGERI 1 KECAMATAN HARAU - Poni Ernis (Inovasi Pendidikan, 2017)
This research is motivated learning outcomes Indonesian subjects in class X MIA 3 still unsatisfactory. One cause less interesting subjects, because it has not developed methods. This type of research is conducted action research (PTK). The subjects were students of class X MIA 3 the first semester of school year 2016-2017 SMA Negeri 1 Subdistrict Harau early July to December period totaling 38 students. This classroom action research using a model developed by Kemmis and Mc. Teggart, consisting of two cycles each cycle consisting of planning (Plan), action (action), observations (observation), and contemplation (reflection). Implementation of each cycle consisting of 2 meetings with the details of two meetings to implement the learning process of one session (2 x 45 minutes) for daily tests. Further elaborated on the operational measures implemented during the three meetings in each cycle that includes planning, implementation, observation, and reflection. Based on the results of this study concluded that the study conducted by researchers at two cycles, it can be seen that the expository approach and inquiry by using group discussions can increase student interest in learning the Indonesian language as an interest to ask the first cycle ride in cycle II. Where that is where we look at the percentage of the first meeting were asking questions that only 16.21% 2.63% recorded speech and the following study by 13.15%. And after it was tested again at a meeting II results obtained can be increased from the previous one.  Keywords: role, methods, discussion, and students